Description of physiotherapy services in a mental health institution in Nigeria - C.A. Gbiri; A.O. Akinpelu; A.C. Odole (AOSIS, 2011)
Physiotherapy  has  long  been  recognised  as  adjunct  to  drug therapy in the management of individuals with mental illness. however, little evidence existed on the utilization of physiotherapy in mental health especially in developing worlds.This study reviewed the utilization of physiotherapy in a Mental health  Institution in lagos, nigeria and determined its contribution to quality of  patient-care in the hospital.This study involved review of clients' activity profile and patients' record in a federal neuro-psychiatric hospital in lagos, nigeria between 2002 and 2006. The hospital records were used as source of information for socio- demographic details. Information on the physical diagnosis was extracted from the patients' records in the departmental records. Data were summarized using descriptive statistics.Six thousand, four hundred and seventy-three (3.3%) out of the 195,686  patients of the hospital within the study period enjoyed physiotherapy ser vices. only 766 (14%) of the hospital in-patients enjoyed physiotherapy services. In addition, 808 clients enjoyed the health promotion services. low back pain (85; 21.7%), osteo-arthritis (82; 20.9%), stroke (64; 16.3%) and shoulder pain  (29; 7.4%) were the most common co-existing health problems referred for physiotherapy.The importance of physiotherapy in mental health is evidenced in the number of patients/clients who benefited from its services. Therefore, physiotherapy is an integral and indispensible member of the mental health team. however, physiotherapy  is  still  under-utilized  in  the  hospital.  This  points  to  the  need  for  proper  integration  of  physiotherapy  into mental health team in the hospital and other similar health institutions.